Plunge Pool Scour Studies Using Cohesive Materials in a Hydraulic Model - Coran, Samuel R. (Philippine Engineering Journal, 2021)
Rocks in situ do not slump and the traditional technique of using loose gravel in the model consequently cannot give a good representation of scour patterns in the prototype. Thus, a refined modelling technique utilizing cohesive materials (a mixture of granular materials with a paste composed of clay binder, chalk powder, and water) to simulate the plunge pool geology is introduced. This technique is applied to the plunge pool scours investigations in a 1:100 hydraulic scale model of a spillway project for the purpose of defining an adequate flip bucket toe protection system. The methods, procedures, and results of the investigations are presented.